Hadith Values and HOTS in Deradicalization: A Curriculum Design to Foster Critical Thinking and Counter Radicalism - Nuhdi, Asep; Muslimin, JM; Primarni, Amie (LP. Ma'arif Janggan Magetan, 2025)
The phenomenon of radicalism among youth and students necessitates the development of an Islamic education curriculum that not only promotes the values of religious moderation but also cultivates Higher Order Thinking Skills (HOTS). This study aims to identify the values of religious moderation found in hadith and analyze their relevance for designing a deradicalization-oriented curriculum integrated with HOTS. Employing a qualitative descriptive approach through library research, primary data were sourced from authentic hadith books such as Sahih al-Bukhari, Sahih Muslim, and Sunan Abu Dawud, while secondary data were drawn from literature related to Islamic education, HOTS, and curriculum studies. Content analysis was used to extract moderation values, and thematic synthesis was applied to map these values onto HOTS indicators: analysis, evaluation, and creation. The findings highlight five key values from hadith—tolerance (tasamuh), justice, deliberation, non-violence, and respect for diversity—which can be systematically integrated into the curriculum to foster critical and inclusive thinking among students. The originality of this study lies in its theoretical model that bridges prophetic values and cognitive frameworks, a rarely explored intersection. A major limitation is the absence of empirical testing, and future research is recommended to implement and evaluate the proposed model in educational settings. In conclusion, integrating hadith values into HOTS-oriented curricula can play a transformative role in shaping moderate and high-thinking learners, and serve as a strategic response to the challenge of radicalism in education.